2020
DOI: 10.1186/s13028-020-00542-2
|View full text |Cite
|
Sign up to set email alerts
|

A modified Sydney system for the diagnosis of chronic gastritis in dogs

Abstract: Background The Sydney system for assessing inflammatory lesions in the gastric mucosa is based on endoscopic and histological examinations. This study aimed to apply the Sydney system to diagnose gastritis in dogs. The study also compared the results of endoscopic and histological examinations conducted on gastric mucosal biopsy specimens. A total of 56 dogs with chronic vomiting were analyzed in the study. The physical appearance of the gastric mucosa was assessed through endoscopic examination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Chronic gastritis is a chronic inflammatory disease of the gastric mucosa characterized by various etiologies (Spużak et al, 2020), one of which is Helicobacter pylori (Hp) (Nagy et al, 2016;Kalach et al, 2021). Previous studies have shown that prevalence, grade and severity of chronic gastritis increases with the degree of Hp infection (Tiwari et al, 2020;Chitapanarux et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic gastritis is a chronic inflammatory disease of the gastric mucosa characterized by various etiologies (Spużak et al, 2020), one of which is Helicobacter pylori (Hp) (Nagy et al, 2016;Kalach et al, 2021). Previous studies have shown that prevalence, grade and severity of chronic gastritis increases with the degree of Hp infection (Tiwari et al, 2020;Chitapanarux et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…нітні форми ХГД об'єднані в одну нозологічну одиницю, однак дана патологія є поліетіологічною [2][3][4]. Результати більшості наукових досліджень останніх років дали змогу з нових позицій переглянути традиційні уявлення про патогенез ХГД.…”
unclassified